More inclusion strategies that work! : aligning student strengths with standards - Karten, Toby J. (Corwin Press, 2007)
Provides research-based strategies for identifying and meeting the needs of students with disabilities, links best inclusive practices with content-specific curriculum, and helps educators fulfill IDEA 2004 requirements.